Inferior Hip Dislocation - A Case Report and Literature Review - Ankur Deshwal; Parvendra Singh; Jashandeep Singh Chahal; Nikhil Relwani; Ishan Mittal; Akanksha Soni (Journal of Orthopaedic Case Reports)
Introduction: Inferior hip dislocation, also known as luxatio erecta femoris, is a rare condition where the femoral head dislocates downward from the acetabulum, typically due to high-energy trauma, such as motor vehicle accidents or falls. We describe a case of Inferior hip dislocation managed by closed reduction. Case Report: A case of inferior dislocation of the hip is described. The case involves a 60-year-old male patient who was brought to the emergency department following a fall from height with pain and externally rotated left lower limb with 70° flexion at left hip joint and 90° flexion at left knee joint. Patient was thoroughly examined and vitally stabilized, followed by X-ray of pelvis with bilateral hips. The X-ray was suggestive of an inferior dislocation of the left hip. Closed reduction under short-duration general anesthesia was done. Adequate reduction was achieved and the patient was followed up. Conclusions: Inferior dislocation of the hip is a rare dislocation of the hip. Treatment with closed reduction under anesthesia is an easy and safe method.